Estimation of single crop co-efficient for wheat crop using spectral indices - Syed Muhammad Saleh; Abdul Latif Qureshi; Irfan Ahmed Shaikh (NAROTAMA UNIVERSITY, Indonesia, 2022)
The majority of the time, real crop water requirements are determined by combining references evaporation with crop coefficients. The crop coefficient accounts for plant transpiration and soil evaporation. The Kc values calculated with the lysimeter setup are point valued with no spatial fluctuation. Remotely detected spectral indices were used to estimate the crop coefficient in both space and time. As a result, this research was carried out to show that crop coefficients may be estimated using satellite data. The corrected satellite data for the research region were obtained/downloaded from the USGS website for the winter growing season (November to March). A hand-held GPS device was used to acquire ground truth valued. Plant heights of randomly selected plants were measured at 15 days intervals at the same time. The downloaded satellite data yielded two spectral indices: the Normalized Difference Vegetation Index (NDVI), and Soil Adjusted Vegetation Index (SAVI).to build relationships between Kc values and spectral indices, basic linear and multiple linear regression approaches were used kc and NDVI had a great individual relationship (R2=0.92) and SAVI (R2=0.79) while the combined association of NDVI and SAVI (R2=0.94) was shown to be superior than each index’s standalone relationship. These relationships should be used to determine Kc values for wheat grown in dry areas with plenty of water.